Death-associated odors induce stress in zebrafish - Oliveira, Thiago Acosta; Koakoski, Gessi; Motta, Adriana Costa da; Piato, Angelo Luis; Barreto, Rodrigo Egydio [UNESP]; Volpato, Gilson Luiz [UNESP]; Gil Barcellos, Leonardo Jose (Elsevier B.V., 2014)
Living animals exploit information released from dead animals to conduct adaptive biological responses. For instance, a recently published study has shown that avoidance behavior is triggered by death-associated odors in zebrafish. Stress can clearly act as an adaptive response that allows an organism to deal with an imminent threat. However, it has not been demonstrated whether these chemical cues are stressful for fish. Here, we confirmed that dead zebrafish scents induce defensive behavior in live conspecifics. Additionally, we show for the first time in fish that these scents increase cortisol in conspecifics. To reach this conclusion, firstly, we exposed zebrafish to multi-sensorial cues (e.g., visual, tactile, chemical cues) from dead conspecifics that displayed defensive behaviors and increased cortisol. Also, when we limited zebrafish to chemical cues from dead conspecifics, similar responses arose. These responses coincide with the decaying destruction of epidermal cells, indicating that defensive and stress responses could take place as an effect of substances emanating from decaying flesh, as well as alarm substance released due to rupture of epidermal cells. Taken together, these results illustrate that living zebrafish utilize cues from dead conspecific to avoid or to cope with danger and ensure survival. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Danio redo; Stress; Cortisol; Necrophobic behavior; Freezing